Nasal Anthropometry among Term and Preterm Indian Neonates- Does Size Matter? - Jain, Ashish; Chitgupikar, Sudharshan Raj; Bhardwaraj, Madhavi; Subramanian, Preethi (Journal of Nepal Paediatric Society, 2022)
Introduction: The binasal prongs are used in neonatal intensive care unit (NICU) to provide nasal Continuous Positive Airway Pressure (n-CPAP) in preterm neonates. A variable degree of nasal trauma is the most common complication of n-CPAP therapy. This can be reduced by use of appropriately sized binasal prongs that are customized to the anatomical measurements of noses. The aim was to estimate the nasal two-dimensional anthropometrical parameters among Indian neonates across different gestations; to compare between both sexes and between neonates with different intra uterine growth status and gestational ages. Methods: Hundred and one neonates across different gestational ages (24 – 42 weeks) and intrauterine growth status who were admitted to the NICU of a tertiary teaching hospital were enrolled and grouped into five categories based on their gestational ages viz. 37 – 42 weeks, 34 – 36 weeks, 31 – 33 weeks, 28 – 30 weeks, and 24 – 27 weeks. Seven nasal and para-nasal measurements were taken (nostril width, nostril length, columella width, columella length, nose width, nose length and philtrum length) for each neonate using a vernier caliper. Results: All anthropometrical measurements differed significantly across gestations especially between 37 - 42 and 24 - 27 wks (p = 0.00). Males differed from females only with respect to nostril width (p = 0.032). The measurements varied significantly when compared among small for gestational age, appropriate for gestational age and large for gestational age neonates. Conclusions: The nasal parameters differed significantly among various GA and intra-uterine growth statuses, which should help design appropriate sizes of bi-nasal prongs.